An examination on the appointment and jurisdiction of women judges in the Selangor syariah court / Noor Hardiani Azhari …[et al.] - Azhari, Noor Hardiani; Mohamad Yusof, Sazwani; Abdul Wahab, Nur Aisyah; Mohd Sukri, Aini Salbia (2011)
Two syariah women judges were recently appointed in the Federal Territory of Putrajaya and Kuala Lumpur. The appointment of women as judges in Muslim countries remains a controversial issue, due to a general perception that such appointment might not be in conformity with the syariah. The purpose of this research is to enlighten one of the contemporary legal dilemmas in Islamic law namely, the appointment of women judges in Malaysia. The methodology employed is library based research. This research will examine on the appointment and jurisdiction of women judges in Malaysian Syariah Court especially in the State of Selangor. There are various views that have been put forward in this research with regards to this topic. The focus of this research is to determine the legal status of appointment of women judges in Syariah Court. It is argued that women judges can be appointed in Muslim countries and that the main reason for this is the fact that there is no explicit prohibition of it in the fundamental sources of Islamic Law. There are also various opinions given by jurists regarding the jurisdiction of this women judges and which one was adopted in Malaysia. The outcome of this research is to prove that no appointment of women judges is required in Selangor Syariah Court as stated in the fatwa issued by the Jabatan Mufti Selangor.